The troop - Cutter, Nick (Gallery Books, 2014)
Once every year, Scoutmaster Tim Riggs leads a troop of boys into the Canadian wilderness for a weekend camping trip. This year, something is waiting in the darkness. Something wicked ... An intruder stumbles upon their campsite like a wild animal. He is shockingly thin, disturbingly pale, and voraciously hungry. Within his body is a bioengineered nightmare, a horror that spreads faster than fear. One by one, the boys will do things no person could ever imagine ...